Association between a common missense variant in LOXL3 gene and the risk of non‐syndromic cleft palate. (11th June 2018) - Khan, Mohammad Faisal J.; Little, Julian; Mossey, Peter A.; Steegers‐Theunissen, Régine P.M.; Bonsi, Martina; Bassi Andreasi, Rita; Rubini, Michele
ABSTRACT: To investigate possible association between functional common variants in the lysyl oxidase like 3 gene and non‐syndromic cleft palate we selected a common missense variant p.Ile615Phe (rs17010021), which was predicted to have a probably damaging effect on the lysyl oxidase like 3 enzyme. We genotyped 258 non‐syndromic cleft palate case‐parent triads of European origin and tested genetic association using the transmission disequilibrium test and log‐linear regression analyses of genotypic relative risks and of parent‐of‐origin effects. The observed genotype frequency in parents was in Hardy–Weinberg equilibrium. Compared with wild‐type Ile/Ile homozygotes, the relative risks for Phe/Phe homozygote infants was 6.87 ( P value 3.0 × 10 −3 ), while that for Ile/Phe heterozygotes was not significant. Assuming an autosomal recessive model, the relative risks for Phe/Phe genotype resulted 10.54 ( P value 2.9 × 10 −5 ), with a 3.6% population attributable risk. No parent‐of‐origin effect was observed. The identification in lysyl oxidase like 3 of a missense variant which under a recessive model associates with 10‐fold increased risk of non‐syndromic cleft palate supports the hypothesis that the genetic etiology of this congenital anomaly includes relatively uncommon recessive variants with moderate penetrance and located in genes which are also involved in syndromes that include cleft palate as part of the phenotype. Our findings require functional validation and replication in a larger independent genetic association study.